Prevalence of Visceral Schistosomiasis in Cattle Slaughtered in North-Eastern Region of Bangladesh - Abdullah, SM; Mohanta, Uday Kumar (Research in Agriculture Livestock and Fisheries, 2021)
A cross sectional study was conducted to estimate the prevalence and identify possible risk factors (season, sex) of Schistosoma in three north-eastern districts of Bangladesh namely Mymensingh, Sunamganj, Kishoreganj. Mesenteric sample of cattle from different slaughter houses were collected and examined for helminths which were identified as Schistosoma on accordance with Soulbsy, 1965. Total 67 (55.83%) out of 120 randomly selected samples were found positive for schistosomiasis. Cattle of Kishoreganj were mostly infected (67.50%), followed by Sunamganj (55.00%) and Mymensingh (45.00%). Regarding seasonal prevalence, samples collected during winter (63.33%) were more infected than summer (48.33%). Moreover, 58.69% of male and 46.42% of female were found infected. In conclusion, relatively high prevalence was recorded in the study areas based on the results obtained. Hence, control measures against schistosomiasis must be designed. Res. Agric., Livest. Fish.8(1): 165-169, April 2021